Cerebral Infarction with Cerebral Thrombosis in Crohn’s Disease: A Case Report - Niharika Reddy; Sarkis Morales Vidal (Acta Neurologica Taiwanica)
We describe a case report of a young male with Crohn’s disease who presented with cerebral infarction and cerebral thrombosis. The patient’s Crohn’s disease had been in remission for 7 years without any recurrent strokes during this period. Our case highlights the need to consider inflammatory bowel disease as a potential cause of stroke in young patients and underscores the importance of managing the condition to reduce recurrent stroke risk.